Association between patient satisfaction with complete dentures and oral health-related quality of life: two-year longitudinal assessment - Stober, Thomas; Danner, Daniel; Lehmann, Franziska; Séché, Anne-Christiane; Rammelsberg, Peter; Hassel, Alexander J. (Clinical oral investigations, 2012)
The objective was to evaluate the development of oral health-related quality of life (OHRQoL) in patients with complete dentures and the association between OHRQoL and patient satisfaction. Fifty-two patients (mean age, 66.3, 48.1% male) received dentures in at least one jaw. The analysis was conducted on participants with dentures in both jaws (CD-Both; n = 22) or in the upper jaw only (CD-Max; n = 28). Data were collected 4 weeks, 6 months, and 1 and 2 years after insertion. OHRQoL was measured by use of the OHIP-EDENT. Self-rated patient satisfaction was assessed on a scale of 0-10. To prove the hypothesis that patient satisfaction would be a meaningful predictor of OHRQoL, and not vice versa, multilevel analysis and cross-lagged correlation analysis were performed for both groups separately. OHRQoL improved from 22.9 (SD, 20.7) to 12.1 (SD, 14.5) for CD-Both and from 20.3 (SD, 17.2) to 14.7 (SD, 15.1) for CD-Max. Multilevel analysis revealed that patient satisfaction and OHRQoL were significantly associated (p < 0.0001) for both groups. Differences between the groups were found with regard to the effect of time after insertion and the interaction between time and satisfaction with OHRQoL which were significant only for the group CD-Both; however, no evidence was found for the causality of this association in the cross-lagged analysis for both groups (ZPF test, p > 0.016). Patient satisfaction and OHRQoL were associated for wearers of complete dentures. Within the limitations of the study, however, the causality that patient satisfaction predicts OHRQoL, and not vice versa, could not be proven.
Published online: 3 November 2010
Gesehen am 28.08.2020